CHANGES IN STOCK VALUES UNDER ACCOUNTING DISCLOSURE TRANSPARENCY: AN EMPIRICAL STUDY ON A SAMPLE OF IRAQI BANKS REGISTERED ON THE IRAQ STOCK EXCHANGE - Khalaf Abdullah Hassan (Scholars Digest Publishing, 2024)
This investigation aims to determine the range of the impact of accounting revelation transparency on changes in stock values by analyzing a sample of banks registered on the Iraq Stock Exchange. The study focused on an illustration of 10 banks registered on the Iraq Stock Exchange. Stock Exchange for the period from 2014 to 2023. Data were composed from the annual reports of the Iraq Stock Exchange and various financial and statistical approaches were used to evaluate the data, including the use of SPSS and Excel programs, the application of skewness, kurtosis, Pearson correlation coefficient, mean and standard deviation. The research concluded several outcomes, the greatest important of which is the being of a significant positive association between accounting disclosure transparency and stock value. A high level of transparency in accounting disclosure is usually escorted by an upsurge in the value of the banks' Stocks in the trial. Moreover, a high level of transparency in accounting disclosure positively affects Stock value by increasing the value of the stocks of the banks included in the study.
Keywords: Stock value, factors affecting changes in stock value, accounting disclosure transparency.